A Muslim conspiracy in British India? :Politics and paranoia in the Early nineteenth century ocean - Chandra Mallampalli (CUP, 2017)
"As the British prepared for war in Afghanistan in 1839, rumours spread of a Muslim conspiracy based in India's Deccan region. Colonial officials were convinced that itinerant preachers of jihad--whom they labelled 'Wahhabis'--were collaborating with Russian and Persian armies and inspiring Muslim princes to revolt. Officials detained and interrogated Muslim travellers, conducted weapons inspections at princely forts, surveyed mosques, and ultimately annexed territories of the accused. Using untapped archival materials, Chandra Mallampalli describes how local intrigues, often having little to do with 'religion,' manufactured belief in a global conspiracy against British rule. By skillfully narrating stories of the alleged conspirators, he shows how fears of the dreaded 'Wahhabi' sometimes prompted colonial authorities to act upon thin evidence, while also inspiring Muslim plots against princes not of their liking. At stake were not only questions about Muslim loyalty, but also the very ideals of a liberal empire"--Provided by publisher.